Capabilities in Physical Education: A Comparative Analysis of School Heads’ and Teachers’ Perspectives - Mendoza, Davidsol; Calabia, Maryjane (CV Rezki Media, 2024)
Background: Effective education delivery relies on PE teachers’ abilities. Research indicates that students’ school performance significantly depends on the quality of PE teaching. Objectives: This study focused on assessing instructional capabilities in physical education. Specifically, it examined how school heads and teachers evaluated teachers’ abilities in content knowledge, pedagogical skills, communication, and professionalism. Additionally, the study compared assessments between the two groups. Methods: The study employed a descriptive research design involving 98 physical education teachers and 59 school heads from the Division of Batangas City. Data collection utilized a researcher-made questionnaire and interviews. Statistical analysis involved weighted mean and independent t-tests for data interpretation. Results: The assessment revealed valuable insights regarding PE teachers’ instructional capabilities. Administrators acknowledged strengths in lesson introduction and accurate content delivery. However, areas for improvement included integrating key elements and promoting higher-order thinking skills. PE teachers felt confident introducing lessons but recognized a need to refine performance demonstrations. Administrators praised diverse teaching methods but suggested creating more challenging experiences. Communication skills were positive, with room for improvement in grammatical accuracy. PE teachers expressed dedication to student physical education but identified a need for more decisive leadership in school-based activities. The findings highlighted specific improvement needs while emphasizing contrasting perceptions between administrators and PE teachers. Conclusion: The assessment found that physical education (PE) teachers are capable in delivering junior high school PE. However, they need familiarity with emerging trends to enhance instruction. School heads and PE teachers have differing views on instructional capabilities, attributed to assessment sources: administrators rely on scheduled observations, while PE instructors use self-assessment and daily teaching experiences.